Monocyte epigenetics and innate immunity to malaria: yet another level of complexity?. Issue 11 (October 2022) - Dobbs, Katherine R.; Dent, Arlene E.; Embury, Paula; Ogolla, Sidney; Koech, Emmily; Midem, David; Kazura, James W.
Graphical abstract: Highlights: Age should be considered in studies that address the role of the epigenome in naturally acquired immunity to malaria. Prospective studies of malaria immunity that address the temporal stability of epigenome modifications are needed. Interrogation of epigenetic markers should be incorporated into multi '-omic' studies of malaria immunity and pathogenesis. Abstract: Children under the age of 5 years living in areas of moderate to high malaria transmission are highly susceptible to clinical malaria with fever that prompts treatment of blood stage infection with anti-malarial drugs. In contrast, older school age children frequently experience subclinical malaria, i.e. chronic Plasmodium falciparum parasitemia without fever or other clinical symptoms. The role of innate immune cells in regulating inflammation at a level that is sufficient to control the parasite biomass, while at the same time maintaining a disease-tolerant clinical phenotype, i.e., subclinical malaria, is not well understood. Recent studies suggest that host epigenetic mechanisms underlie the innate immune homeostasis associated with subclinical malaria. This Current Opinion article presents evidence supporting the notion that modifications of the host monocyte/macrophage epigenome regulate innate immune functions pertinent to subclinical malaria.